FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS TIDUR PASIEN POST OPERASI LAPARATOMI DI RUANG RAWAT INAP RUMAH SAKIT PKU MUHAMMADIYAH GOMBONG - nurlela, siti; -, saryono; yuniar, isma (Jurnal Ilmiah Kesehatan Keperawatan, 2009)
Laparatomy is one of the operation procedure that perform in the abdominal  area. That procedure sometimes will cause increasing patients anxiety and disturbance of patient’s sleep quality. The researched purpose is to know the dominance factor that influence sleep quality of patient post laparatomy at PKU Muhammadiyah Gombong Hospital. This research was a survey with cross sectional approach. The sampling method used was accidental sampling and was got 25 patents. Analysed use d was univariat, bivariat and multivariate with logistic regression. Chi Square statistic test of physiologic factor at X²=4,001 and p=0,045 (<0,05) so there is a correlation between physiologic factor and sleep quality of patient with post laparatomy at PKU Muhammadiyah Gombong Hospital. Odd Ratio value has 0,983 or 98,3%. Chi Square statistic test of psychology factor has X²=14,005 and p=0,000 (<0,05) so there is a correlation between psychology factor and sleep quality of patient with post laparatomy in PKU Muhammadiyah Gombong Hospital. Odd Ratio value at 0,717 or 71,7%. Chi Square statistic test of environmental factor has X²=6,177 and p=0,013 (<0,05) so there is a correlation between environmental factor and sleep quality of patient with post laparatomy in PKU Muhammadiyah Gombong Hospital. Odd Ratio value at 0,089 or 8,9%. The Biggest Odd Ratio is physiologic factor  with value at 0,983 or 98,3% it mean that physiologic factor has influenced sleep quality of patient with post lapratomy in PKU Muhammadiyah Gombong Hospital. There is a correlation between physiology, psychology and environment factors with sleep quality of patient post laparatomy in PKU Muhammdiyah Gombong Hospital and dominance factor to influence sleep quality of patient post laparatromy in PKU Muhammadiyah Gombong Hospital is physiology   Keywords: Sleep quality, post laparatomy.